Efek Mediasi Moderasi Disiplin Kerja Terhadap Kinerja Karyawan Pada Perusahaan Jasa Pengiriman XYZ di Jakarta - Yustinus Yuniarto; Vina Apriyana; Michael Christian; Suryo Wibowo; Sunarno Sunarno (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. The logistics service industry, especially courier services or delivery of goods, is increasingly attractive as the number of players in this business continues to grow. Organizations are trying to increase the distribution of agent points to reach more users of freight forwarding services. In this regard, the readiness of the organization in preparing human resources who are ready to work must be planned. Recruitment, training, or training strategies to career path opportunities must be designed as accurately and as attractively as possible to support optimal employee performance to support the success of organizational performance. This study aims to analyze the determinants of employee performance at the courier service company PT XYZ in Jakarta by using work discipline as a mediator and moderator variable. This quantitative research uses structural modeling with a Partial Least Square approach. To analyze the data, this study used SMART PLS 3.0. The sample of this research is the employees of PT XYZ, totalling 59 people based on the criteria that have been determined in this study. The results of this study explain that on the mediating effect, work discipline acts as a mediator of employee career development on employee performance but does not mediate training programs provided by employees in shaping employee performance.Abstrak. Industri jasa logistik khususnya jasa kurir atau pengiriman barang semakin menarik seiring dengan terus bertambahnya pemain pada bisnis ini. Organisasi berusaha meningkatkan sebaran-sebaran titik agen untuk menjangkau lebih banyak pengguna jasa pengiriman barang. Berkaitan dengan hal ini, kesiapan organisasi dalam menyiapkan sumber daya manusia yang siap kerja harus direncakan. Strategi perekrutan, training atau pelatihan sampai kepada kesempatan jenjang karir harus didesain setepat dan semenarik mungkin untuk menunjang kinerja karyawan yang optimal guna mendukung keberhasilan kinerja organisasi. Penelitian ini bertujuan untuk menganalisis determinan kinerja karyawan di perusahaan jasa kurir PT XYZ di Jakarta dengan menggunakan variabel work discipline sebagai pemediasi dan pememoderasi. Penelitian kuantitatif ini menggunakan pemodelan struktural dengan pendekatan Partial Least Square. Untuk menganalisis data, penelitian ini menggunakan SMART PLS 3.0. Sampel penelitian ini yaitu karyawan PT XYZ yang berjumlah 59 orang yang didasarkan pada kriteria yang telah ditentukan pada penelitian ini. Hasil penelitian ini menjelaskan bahwa pada efek mediasi, work discipline berperan sebagai pemediasi development karir karyawan terhadap kinerja karyawan namun tidak memediasi program pelatihan yang diberikan karyawan dalam membentuk kinerja karyawan.